2011
DOI: 10.1111/j.1475-4754.2010.00544.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution (Pixe) Analyses of Carbonate Deposits in a Roman Aqueduct (Fréjus, Se France): Implications for the Study of Palaeohydrological Variability and Water Resources Management in Southern Gaul During the Roman Period*

Abstract: Urban water was supplied to the Roman city of Forum Julii (Fréjus, southeastern France) for at least 200 years by a 39.4 km long aqueduct, operating in ad 50. Two perennial springs were successively collected, the Foux and the Siagnole, located at the outlet of Triassic and Jurassic karstic reservoirs, respectively. In this study, we performed high‐resolution PIXE (Particle‐Induced X‐ray Emission) measurements of Ca, Si, Fe and Sr concentrations on selected cross‐sections of laminated carbonate sampled along t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 57 publications
(84 reference statements)
0
12
0
5
Order By: Relevance
“…Adolphe () and Guendon & Vaudour () found evidence for microbiological activity in calcareous sinter and claimed that this may have influenced the formation of the micritic laminae. These micritic laminae are enriched in Fe, Si and Al, possibly due to the presence of clay minerals (Rodier et al ., ; Guendon et al ., ; Carlut et al ., ; Bobée et al ., ). Guendon et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Adolphe () and Guendon & Vaudour () found evidence for microbiological activity in calcareous sinter and claimed that this may have influenced the formation of the micritic laminae. These micritic laminae are enriched in Fe, Si and Al, possibly due to the presence of clay minerals (Rodier et al ., ; Guendon et al ., ; Carlut et al ., ; Bobée et al ., ). Guendon et al .…”
Section: Introductionmentioning
confidence: 97%
“…() published some spot δ 18 O analyses for the Fréjus aqueduct (southern France) showing a very similar range for different lamina couplets. Trace‐element data of calcareous sinter deposits were successfully applied to determine the provenance of water for the aqueducts of Fréjus and Pompeii, both of which were fed by more than one source (Ohlig, ; Guendon et al ., ; Bobée et al ., ). Finally, a number of previous studies tried to use calcareous sinter deposits in aqueducts to obtain information on palaeoseismicity (Meghraoui et al ., ; Volant et al ., ; Galli et al ., ; Sbeinati et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Whilst there have been some studies on the possible water-carrying capacity of Roman aqueducts (for example Keenan-Jones et al (2015); Motta et al (2017) previously cited). A few, including Bobée et al (2011) and Keenan-Jones (2013) have considered the amount of water available to flow into the aqueducts at various seasons, including some consideration of possible variations between ancient and modern times. Given the size and complexity of the Valens aqueduct catchment, the amount of water obtainable, or in modern terms, the hydrology of the catchment, must have been a serious consideration for its Roman designers.…”
Section: Water Available For Usementioning
confidence: 99%
“…As a typical example of PIXE application in the research field of geochemistry, the laminated carbonate deposited on the side walls of Roman aqueducts was measured by PIXE . It was found that the thick and clear laminae of the carbonate layers were enriched with Sr, while Fe and Si were depleted in the thin and dark laminae.…”
Section: Applicationsmentioning
confidence: 99%